2018
DOI: 10.1111/dom.13450
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia risk in the first 8 weeks of titration with insulin glargine 100 U/mL in previously insulin‐naive individuals with type 2 diabetes mellitus

Abstract: Patient characteristics associated with hypoglycaemia frequency during insulin glargine 100 U/mL (Gla-100) titration and clinical outcomes at Week 24 were examined using participant-level data from 16 treat-to-target trials involving individuals with type 2 diabetes mellitus who were inadequately controlled with oral antidiabetes drugs and were initiating Gla-100 (n = 3549). Hypoglycaemia (plasma glucose <3.9 mmol/L or severe) during the first 8 weeks of titration was stratified by number of events (0, 1-3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Results showed that the incidence of anytime (24 hours) hypoglycaemic events within the maintenance period (weeks 13–24) was lower for individuals who did not experience hypoglycaemia within the initial 12‐week titration period compared with those who did (38.2% vs. 75.4%) . Additionally, an analysis of 16 RCTs of Gla‐100 initiation showed that a higher risk of hypoglycaemia during titration was associated with a continued higher risk of non‐severe and severe hypoglycaemia for up to 6 months …”
Section: The Clinical Importance Of the Titration Periodmentioning
confidence: 99%
“…Results showed that the incidence of anytime (24 hours) hypoglycaemic events within the maintenance period (weeks 13–24) was lower for individuals who did not experience hypoglycaemia within the initial 12‐week titration period compared with those who did (38.2% vs. 75.4%) . Additionally, an analysis of 16 RCTs of Gla‐100 initiation showed that a higher risk of hypoglycaemia during titration was associated with a continued higher risk of non‐severe and severe hypoglycaemia for up to 6 months …”
Section: The Clinical Importance Of the Titration Periodmentioning
confidence: 99%
“…For example, experiencing hypoglycemia early after the initiation of basal insulin (BI) is associated with a higher long-term risk of hypoglycemia or BI discontinuation. 8,9 Clinician concerns about hypoglycemia may result in suboptimal treatment 10 and contribute to many people with T2D not achieving the target glycated hemoglobin (HbA1C) levels. 11 The adjustment of insulin doses in patients with T2D is often led by healthcare providers (HCPs), but access to timely and appropriate HCP resources and education to support effective self-titration remain challenging.…”
Section: Introductionmentioning
confidence: 99%
“…7 Therefore, reducing the risk of hypoglycaemia during this period may be particularly beneficial, 6 as both randomized controlled trials and real-world evidence have shown an association between experiencing hypoglycaemia soon after initiating BI therapy and a higher risk of hypoglycaemia and BI discontinuation in the longer term. [8][9][10] In addition, reducing hypoglycaemia during the titration period may increase confidence to up-titrate BI. This is important because failure to reach an HbA1c of <7.0% by 3 months is associated with an increased risk of failing to achieve this target at 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…Previous real‐world studies have also shown that active titration of basal insulin (BI) typically occurs during the first 12 weeks, after which there is little further titration . Therefore, reducing the risk of hypoglycaemia during this period may be particularly beneficial, as both randomized controlled trials and real‐world evidence have shown an association between experiencing hypoglycaemia soon after initiating BI therapy and a higher risk of hypoglycaemia and BI discontinuation in the longer term . In addition, reducing hypoglycaemia during the titration period may increase confidence to up‐titrate BI.…”
Section: Introductionmentioning
confidence: 99%